Angiogenesis in nodal B cell lymphomas: a high throughput study. Issue 5 (21st June 2006) - Tzankov, Alexandar; Heiss, Simone; Ebner, Stephanie; Sterlacci, William; Schaefer, Georg; Augustin, Florian; Fiegl, Michael; Dirnhofer, Stephan
Abstract : Aim: To assess the biological significance of vascular endothelial growth factor (VEGF) A, VEGF receptor (Flk-1) and cyclooxygenase 2 (COX2) expression with respect to microvessel density (MVD), proliferative activity (Ki-67), expression of p53 and clinical presentation in a large cohort of nodal B cell lymphomas. Methods: An immunohistochemical and morphometric study was performed on a validated tissue microarray containing 271 B cell lymphoma specimens, 197 of which included follow-up data. Statistical assessment was done by Pearson's χ 2 test, Spearman's rank correlation coefficient, analysis of variance and survival analysis. Results: 266 (98%) cases were evaluable. Strong VEGF expression was observed in only 20 diffuse large B cell lymphomas (DLBCLs). Flk-1 and COX2 were expressed in 53 and 21 cases, respectively, mainly in DLBCLs, follicular lymphoma (FL) grade 3 and mantle cell lymphomas (MCLs), in a low proportion of cells. MVD decreased in the following order: DLBCLs, FLs, MCLs and small lymphocytic lymphomas/chronic lymphocytic leukaemia (SLL/CLLs). VEGF expression correlated with Ki-67, p53 and COX2 expression in the whole cohort and in DLBCLs. Flk-1 expression correlated with Ki-67 in the cohort and in SLL/CLL and FL grade 1 and 2. COX2 expression correlated with Ki-67 and p53. The analysed angiogenesis parameters did not correlate with clinical parameters or survival. Conclusions: Angiogenesis plays a differential role in various B cell lymphomas. Aggressive lymphomas express the potential molecular therapeutic targets VEGF and COX2, and have higher MVD. In a few low proliferation-fraction lymphomas, Flk-1 might have a role in proliferative advantage. Therapeutic strategies aimed at angiogenesis should take into account lymphoma heterogeneity.